2005
DOI: 10.2135/cropsci2004.0721
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid Acyl Chain and Phospholipase Dynamics during Cold Acclimation of Winter Wheat

Abstract: on the phospholipid profiles. It has been suggested that alterations in concentration of specific phospholipids Phospholipid (PL) composition is known to change in plants explay a role in cold acclimation. Horvath et al. (1979) posed to cold temperature. The dynamics of PL acyl chain pairs and genes encoding phospholipase enzymes were studied in winter wheat observed an inverse relationship between survival and (Triticum aestivum L.) during cold acclimation. Mass spectrometry the loss of phosphatidylcholine by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
9
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
3
9
0
Order By: Relevance
“…1) were consistent with the observations that initial exposure to subzero temperature results in depolymerization of fructan (Livingston and Henson, 1998), and that elevated levels of sucrose induce fructan synthesis (De Roover et al, 2000;Maleux and Van den Ende, 2007), as we observed in the -3,48 h treatment (Fig. We previously demonstrated that the expression levels of some genes encoding phospholipases (Skinner et al, 2005) and phospholipase A 2 enzyme activity (Skinner, 2009a) in wheat crown tissue rapidly increased when the plants were transferred to a cold acclimation-inducing temperature, remained elevated as the plants continued to acclimate and develop greater freezing tolerance, then declined as the acclimation process was completed and the freezing tolerance of the plants began to decline. As these changes in concentrations of sugars were occurring, characteristic changes in lipid species also were occurring.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…1) were consistent with the observations that initial exposure to subzero temperature results in depolymerization of fructan (Livingston and Henson, 1998), and that elevated levels of sucrose induce fructan synthesis (De Roover et al, 2000;Maleux and Van den Ende, 2007), as we observed in the -3,48 h treatment (Fig. We previously demonstrated that the expression levels of some genes encoding phospholipases (Skinner et al, 2005) and phospholipase A 2 enzyme activity (Skinner, 2009a) in wheat crown tissue rapidly increased when the plants were transferred to a cold acclimation-inducing temperature, remained elevated as the plants continued to acclimate and develop greater freezing tolerance, then declined as the acclimation process was completed and the freezing tolerance of the plants began to decline. As these changes in concentrations of sugars were occurring, characteristic changes in lipid species also were occurring.…”
Section: Discussionsupporting
confidence: 90%
“…3). Fatty acids of 12 to 16 carbons are very common acyl sidechains of phospholipids in wheat cell membranes (Skinner et al, 2005); hence, this result is consistent with the observation that small lipids, including free fatty acids derived response to the onset of subfreezing temperature, but that response was transient and largely, but not entirely, dissipated within 48 h, regardless of whether the subfreezing temperature stress was removed or remained constant. 3), suggesting the -3°C, 24 h treatment resulted in the generation of several lipid species in that size range.…”
Section: Lipidssupporting
confidence: 87%
See 1 more Smart Citation
“…2005). We previously demonstrated that exposure of ORFW to 4°C resulted in changes of phospholipid profiles that were similar to changes in ‘Eltan’, ‘Froid’, ‘Kestrel’ and ‘Tiber’, over a 5‐week period of acclimation (Skinner et al. 2005).…”
Section: Discussionmentioning
confidence: 91%
“…Also, given the observation of ‘different genetic mechanisms controlling cold resistance at each temperature level’ (Parodi 1969), the identification of specific genes will require evaluation of inheritance of freezing tolerance at defined temperatures. Winter wheat line ‘Oregon Feed Wheat #5’ (ORFW) was reported to have very little freezing tolerance in controlled temperature studies (Skinner et al. 2005), and in the field (DeNoma 1990).…”
mentioning
confidence: 99%